Involvement of mainstream teachers in inclusive education: are we ready? - Lai, Chee Sern (Universiti Putra Malaysia Press, 2017)
The implementation of inclusive education is a challenging task because the teachers involved in inclusive education must equip themselves with field knowledge and pedagogical skills and, more importantly, they must have great passion for inclusive education. This research attempts to investigate the readiness of mainstream teachers who engaged in an inclusive education programme. Readiness was measured in three different aspects: (i) field knowledge, (ii) pedagogical skill, and (iii) attitude. A total of 128 mainstream teachers who were actively involved in inclusive education programmes in primary schools were invited to participate in this research. A questionnaire was constructed to measure the level of readiness among the participating teachers. The results revealed that although the readiness level in terms of pedagogical skill was high, the readiness for field knowledge and attitude were at medium level. Our findings suggest that more effort and pragmatic actions are required to facilitate mainstream teachers who teach in inclusive classes to enhance their field knowledge and strengthen their positive attitude towards inclusive education.